Evaluation on the thyroid disrupting mechanism of malathion in Fischer rat thyroid follicular cell line FRTL-5. (2nd October 2018) - Xiong, Jingyuan; Tian, Liantian; Qiu, Yongjie; Sun, Ding; Zhang, Hao; Wu, Mei; Wang, Jintao
Abstract: Thyroid hormones are involved in many important physiological activities including regulation of energy metabolism, development of nervous system, maintenance of cerebral functions, and so on. Endocrine-disrupting chemicals (EDCs) that interfere with thyroid functions raise serious concerns due to their frequent misuse in areas where regulations are poorly implemented. In addition, chemicals that are originally regarded safe may now be considered as toxic with the development of life sciences. Malathion is an organophosphate insecticide that is widely applied and distributed in agricultural and residential settings. Due to the low acute toxicity and rapid degradation, malathion is not listed as a primary thyroid disrupting chemical. However, emerging evidences reported that malathion affected thyroperoxidase catalyzed iodide oxidation which in turn influenced thyroid hormone transportation, and enhanced parathyroid hyperplasia prevalence. Nevertheless, direct effect of malathion on thyroid hormone biosynthesis remains to be elucidated. This study investigated the effects of thyroid disruption of malathion in Fischer rat thyroid follicular cell line, FRTL-5. Transcriptional and translational analyses on thyroglobulin demonstrated that both mRNA and protein expression levels were significantly inhibited by malathion. Cellular cAMP level and TSH receptor expression were distinctly reduced by malathion (6.0 µg/ml). These results suggested that malathion directly disrupted the biosynthesis of thyroid hormone and the mechanism involved down-regulation of TSH receptor and cellular cAMP. This subsequently led to the suppression of TSH dependent signal transduction, TG transcription inhibition, and obstruction of thyroid hormone biosynthesis.